Significant Factors of High Performance Outcomes for Tibial Plafond Fractures. (October 2022) - Wheelwright, John C.; Christensen, Garrett V.; Cizik, Amy M.; Zhang, Chong; Marchand, Lucas S.; Haller, Justin M.
Background: Limited research exists about high performance postsurgical tibial plafond fractures. This study aimed to identify aspects of the plafond fracture injury and care associated with "high performance" based on Patient Reported Outcome Measurement Information System (PROMIS) Physical Function (PF) scores. Methods: Tibial plafond fracture patients with minimum 12-month follow-up treated at a level 1 trauma center from 2006 to 2019 were categorized into high (top 25%) vs average-low (AL) (bottom 75%) performers based on PROMIS PF scores. Demographics and fracture characteristics of high and AL performers were compared. Variables with a P value less than .1 were used in stepwise logistic regressions. Results: The final cohort of 198 patients was divided into high (n=51) and AL (n=147) performers based on PF scores. The mean PF scores for the high and AL groups were 58 (SD=5.3) and 41.9 (SD=6.5), respectively. The mean PROMIS Pain Interference scores for the high performers and AL were 43.3 (SD=4.9) and 56.8 (SD=8.6) ( P < .001), respectively. FAAM activities of daily living (high 95.4 [SD=5.5] vs AL 70.4 [SD=19.8], P < .001) and FAAM sports (high 76.8 [SD=21.3] vs AL 27.3 [SD=28.9], P < .001) subscale scores were significantly greater in the high-performing group. Sex, age, marital status, and diabetes were nonsignificant factors in univariate analysis. Significant demographic factors associated with high performance from univariate analysis were Caucasian race, private insurance, no tobacco use, lower body mass index (BMI), and mechanism of injury. Patients with fracture characteristics of OTA 43C (complete articular) fractures, bone loss, open fractures, or nonexcellent reduction were significantly less likely to be high performers. Additionally, less than excellent reductions were more common in more complex fracture patterns. Multivariable regression modeling showed that higher BMI, OTA/AO 43-C (complete articular) fracture classification, and open fracture were significant independent risk factors for reducing likelihood of high performance. Conclusion: Significant independent factors associated with high performance after tibial plafond fracture are lower BMI, closed fracture, and OTA/AO 43-B (partial articular) fracture.